UPAYA MENINGKATKAN KREATIFITAS BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA MENGGUNAKAN GEOGEBRA DENGAN PENDEKATAN PROBLEM POSING - Syariful Fahmi; Soffi Widyanesti Priwantoro (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
Problems in learning introductory computer science which need urgent resolution is the problem related to the creativity of the student learning. Along with the existence of the use of software geogebra to ease the learning of mathematics, as well as the existence of a problem posing approach, the above problem resolution efforts got the right momentum. The learning approach that is used in this research is the h problem posing approach with combined use of software geogebra. As for the purposes of this learning approach is to improve creativity of students learning.This research activity involves two lecturers and 21 students in class introduction of computer science at semester 4 academic year 2015-2016. Student creativity data collected by using a sheet of observation which further analyzed in qualitative descriptive.Based on the results of data analysis it is known that the use of the problem posing approach can raise average student learning where creativity before the cycle 1 is being implemented (score 1.06). While once held a series of activities cycle 2 is known to the average student learning categories include creativity high (score 2.09). This indicates the occurrence of increased creativity learning of students.